HUBUNGAN KELINCAHAN DENGAN KEMAMPUAN MENGGIRING DALAM SEPAKBOLA PADA TIM SMAN 3 SINGINGI HILIR KABUATEN KUANTAN SINGINGI - Arip Kosasih; Drs. Ramadi., S.Pd., M.Kes AIFO '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, The problem in this research is ability to dribbling football is still considered optimal. This is presumably because of agility. The purpose of this study was to determine whether there is a corelation the agility with the ability to dribble the soccer game on a team SMAN 3 Singingi Hilir District of Kuantan Singingi. This research is correlational with a sample size of 25 people by using total sampling technique. The research data was obtained from the measurement results using the zig-zag tun test for agility and dribbling skills test. Based on the research that has been done on the players team SMAN 3 Singingi Hilir District of Kuantan Singingi obtained rcount = 0.594. At the significant level of 5% was found rtabel = 0.396. thus rcount> rtabel or 0.594> 0.396 and rcount categorized strong enough. Tests of significance using the formula t test Significance. From the calculation results are known t = 3.54, while t table = 1.714 so t = 3.54> t table = 1.714. Then it can be concluded as follows: There is a significant corelational between agility with the ability to dribbling the team Football SMAN 3 Singingi Hilir District of Kuantan Singingi by category strong enough because r = 0.594.Keywords : Agility, Dribbling, Soccer